2016
DOI: 10.1007/s11430-015-5243-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of temporal dynamics of snow cover and its validation with hydro-meteorological data in parts of Chenab Basin, western Himalayas

Abstract: The present investigation was conducted to analyze the temporal patterns of snow cover area% (SCA%), air temperature, snowfall and river discharge in parts of Chenab basin, western Himalayas. The relationship of mean SCA% with mean air temperature and river discharge was also tested using Pearson's product-moment correlation at 95% confidence limit and further sensitivity analysis of river discharge to SCA and SCA to air temperature was performed. Moderate Resolution Imaging Spectroradiometer (MODIS) 8-day sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 55 publications
(63 reference statements)
2
8
0
Order By: Relevance
“…Recently, several authors [7,105] have confirmed that SCA and SD are increasing in the mountain regions and that this increase may have positive influences on glacier mass balance. The decreasing runoff trend from increased SCA was also observed in the Chenab Basin of the Himalayas [97]. With the positive trend in precipitation, summertime temperatures in the Kumalak River basin have shown a downward trend at a rate of −0.58 K/decade during 1998-2009 [100].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Recently, several authors [7,105] have confirmed that SCA and SD are increasing in the mountain regions and that this increase may have positive influences on glacier mass balance. The decreasing runoff trend from increased SCA was also observed in the Chenab Basin of the Himalayas [97]. With the positive trend in precipitation, summertime temperatures in the Kumalak River basin have shown a downward trend at a rate of −0.58 K/decade during 1998-2009 [100].…”
Section: Discussionmentioning
confidence: 70%
“…This sensitivity analysis theory, as recommended by Zheng et al [96], was used to evaluate the sensitivity of monthly runoff to SCA/SD in the headwaters of the Yellow River Basins. Kour et al [97] also used the model to detect the monthly river discharge to SCA in the Chenab Basin, Western Himalayas. The equation is given as:…”
Section: Sensitivity and Correlation Analysis Between Snow Cover Areamentioning
confidence: 99%
“…Shafiq et al [19] investigated the snow cover over the Kashmir Himalaya and concluded a significant increasing trend in annual mean SCA and decreasing trends in minimum and maximum temperature from 2000 to 2016. Several studies have also reported the increasing annual SCA trends over the Western Himalayas [11,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term trend analyses were performed using the Modified Mann-Kendall test at monthly, seasonal, and annual levels for the whole study region and the different elevation zones separately. Previous studies [12,19,35,36] analyzing the SCA variation with respect to temperature, precipitation, and DEM have mainly been limited to some river basins or other specific regions. The current study considers the entire NWH region for the most recent 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Observed trends in low flows need to be explained and 38 attributed to their underlying causes. Worldwide, there are few related studies and most of 39 them linked trends in monthly or yearly flows to cumulative precipitation or temperature at the 40 same temporal scale (Mavrommatis and Voudouris, 2007;Khattak et al, 2011;Ling et al, 41 2013;Huang et al, 2014;Li et al, 2014;Kour et al, 2016). In Canada and the USA, trends 42 in low flow HDIs have actually been linked to specific climate data indices (CDIs) computed 43 from cumulative rainfall, precipitation or degree-days over the course of one month up to a 44…”
mentioning
confidence: 99%